m-51=-70

Simple and best practice solution for m-51=-70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-51=-70 equation:


Simplifying
m + -51 = -70

Reorder the terms:
-51 + m = -70

Solving
-51 + m = -70

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '51' to each side of the equation.
-51 + 51 + m = -70 + 51

Combine like terms: -51 + 51 = 0
0 + m = -70 + 51
m = -70 + 51

Combine like terms: -70 + 51 = -19
m = -19

Simplifying
m = -19

See similar equations:

| -112+x=40-7x | | 27m^2=3 | | 2-2-4= | | 1.5y=2.3 | | 4(x-y)+z=2x+z | | -2(x+2)-2x=5x-9 | | 3d=7*21 | | (x^2+4x-6)(x^2+6x-3)= | | 112+x=40-7x | | 0.5(3g-2)=g | | 3x+4y=35 | | d+25=b | | -3h+12-4h=-7h-16 | | -1=(x/4)-3 | | 2(-8+8x)+5x=-100 | | 3x+49=3 | | 3x+3y=20 | | 8c=7*16 | | 3x+2+2x=x+16 | | 2a+3a+4=5a-18 | | x-1=2x-2 | | 315=-5(1-8v) | | 3t-t=-22 | | 458=6x+308 | | -8(-2x-5)-4x=88 | | -34=-4(x+4)-5x | | y=(8-6k)x | | 3y-9x=21 | | 3a=2*12 | | 9(x+8)+6=4(x+7) | | -3x+4+3x-3=5 | | 1.09=1.3h |

Equations solver categories